E-learning Madrasah Efficiency as an Online Learning Tool to Improve Student Learning Outcomes at Madrasah Aliyah Negeri 1 Jombang - Hilyah Ashoumi; Siska Binti Qoirot (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to determine the use of e-learning madrasah during distance learning and also to determine student learning outcomes through e-learning madrasah. This research uses development research. Data collection techniques used questionnaires, validation sheets and also pretest and posttest questions. Therefore, the researchers used the R&D method for processing questionnaires and the Pairet Sample Test to determine student learning outcomes and also regarding the existence of meaningful treatment in conducting research on each variable. This can be seen from the results of the questionnaire given to the respondents showing a percentage of 78% that the E-Learning Madrasah is worthy of being a learning medium at MAN 1 Jombang and the average pretest score is 74 while the posttest value is 84. Based on the pairet sample test table , the significance value is < 0.05 indicating that there is a significant effect on the difference in the treatment given during the pretest and posttest in the subject of aqidah akhlak during the current Coronavirus Disease 2019 (Covid-19) pandemic.